Identification of Novel Genetic Variants in CVID Patients With Autoimmunity, Autoinflammation, or Malignancy - Christiansen, Mette; Offersen, Rasmus; Jensen, Jens Magnus Bernth; Petersen, Mikkel Steen; Larsen, Carsten S.; Mogensen, Trine H. (Frontiers in Immunology, 2020)
Common variable immunodeficiency (CVID) is a primary immunodeficiency characterized by recurrent bacterial infections and defined by reduced levels of IgG, IgA, and/or IgM, insufficient response to polysaccharide vaccination, and an abnormal B-cell immunophenotype with a significantly reduced fraction of isotype-switched memory B cells. In addition to this infectious phenotype, at least one third of the patients experience autoimmune, autoinflammatory, granulomatous, and/or malignant complications. The very heterogeneous presentation strongly suggests a collection of different disease entities with somewhat different pathogeneses and most likely diverse genetic etiologies. Major progress has been made during recent years with the advent and introduction of next-generation sequencing, initially for research purposes, but more recently in clinical practice. In the present study, we performed whole exome sequencing on 20 CVID patients with autoimmunity, autoinflammation, and/or malignancy from the Danish CVID cohort with the aim to identify gene variants with a certain, possible, or potential disease-causing role in CVID. Through bioinformatics analyses, we identified variants with possible/probable disease-causing potential in nine of the patients. Of these, three patients had four variants in three different genes classified as likely pathogenic (NFKB1, TNFAIP3, and TTC37), whereas in six patients, we identified seven variants of possible pathogenic potential classified as variants of unknown significance (STAT3, IL17F, IRAK4, DDX41, NLRC3, TNFRSF1A, and PLCG2). In the remaining 11 patients, we did not identify possible genetic causes. Genetic findings were correlated to clinical disease presentation, clinical immunological phenotype, and disease complications. We suggest that the variants identified in the present work should lay the ground for future studies to functionally validate their disease-causing potential and to investigate at the mechanistic and molecular level their precise role in CVID pathogenesis. Overall, we believe that the present work contributes important new insights into the genetic basis of CVID and particular in the subset of CVID patients with a complex phenotype involving not only infection, but also autoimmunity, autoinflammation, and malignancy.